Oral candidiasis caused by ciclesonide in a patient with COVID-19 pneumonia: A case report and literature review. (September 2021) - Ohashi, Nobuhide; Ideta, Yuka; Takeda, Atushi; Iwai, Toshinori; Kioi, Mitomu; Miyazaki, Akihiro; Mitsudo, Kenji
Steroid has recently been reported as a treatment for new coronavirus disease (COVID-19). The incidence of oropharyngeal candidiasis due to the inhaled steroid ciclesonide is lower than that due to other inhaled steroids. We report the first case of oral candidiasis with COVID-19 pneumonia using ciclesonide. A 75-year-old man was hospitalized for COVID-19 pneumonia. After admission, an oral combination of lopinavir/ritonavir was administered, and ciclesonide was inhaled for 7 days. On the 14th day of hospitalization, white plaque was found in his oral mucosa. Candida albicans was identified by oral bacterial tests, and amphotericin B was initiated. On the 35th hospital day, negative result for C. albicans was confirmed. Intraoral monitoring and intervention by dental care workers are considered important for the prevention of infectious complications induced by corticosteroids.